2022
DOI: 10.33899/ijvs.2021.129934.1702
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of Escherichia coli isolated from milk of cattle affected by mastitis

Abstract: This evolution-based study aimed to reliably identify the epidemiological prevalence of Escherichia coli that was recovered from affected milk of cattle by mastitis, study the evolution of this bacterium, and describe some isolates using polymerase chain reaction (PCR) technique and DNA sequencing. Here, we collected 50 cattle milk samples and submitted them to conventional bacterial isolation and identification using enrichment culture method and biochemical tests. Then, we confirmed the results by PCR techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The present study coliform pathogens high investigate &highly relationship to the score of CMT which is recorded ( 82.9% ) with later research reported high agreement between result of California test with bacteria detection [25]. Among different bacterial pathogens isolated, The current results showed that E. coli at (33.8%), Its agreement pattern was noticed in Iraq by reference [26], which is 36 % as predominant coliform pathogen than other species from milk contamination .further the our result high relatively show than by [27]which is 30% in Egypt. on the other hand, k.pneumonia constituted 11.7 % are the second prevalent bacteria finally Proteus mirabilis investigate as a low presented 10.2% from total isolate similar to [28,29].…”
Section: Identification and Isolationsupporting
confidence: 73%
“…The present study coliform pathogens high investigate &highly relationship to the score of CMT which is recorded ( 82.9% ) with later research reported high agreement between result of California test with bacteria detection [25]. Among different bacterial pathogens isolated, The current results showed that E. coli at (33.8%), Its agreement pattern was noticed in Iraq by reference [26], which is 36 % as predominant coliform pathogen than other species from milk contamination .further the our result high relatively show than by [27]which is 30% in Egypt. on the other hand, k.pneumonia constituted 11.7 % are the second prevalent bacteria finally Proteus mirabilis investigate as a low presented 10.2% from total isolate similar to [28,29].…”
Section: Identification and Isolationsupporting
confidence: 73%
“…Using the Safe-Blue Illuminator/Electrophoresis System, electrophoresis was performed for 50 minutes at 120 volts. By comparing PCR result amplicons to a 100 bp DNA ladder, migration patterns were studied (29,30).…”
Section: Oligonucleotides and Pcr Amplificationmentioning
confidence: 99%
“…Electrophoresis conditions of include (75 V-300 mA -1h) using Wide Mini -Sub Cell GT (BioRad, USA). After that, the gel was observed using the (Gel-doc-Ez) system to revealing the specified bands (16,17).…”
Section: Detection Of Pseudomonas Aeruginosa and Their Virulence Gene...mentioning
confidence: 99%